Chasing safety: Race-day falls and injuries in Irish professional and amateur horseracing from 2016 to 2024 - Reville, A.; Corrigan, J.; Pugh, J.; O'Connor, S. (Journal of Science and Medicine in Sport, 2026)
Objectives This study aimed to: 1) examine fall and injury incidence in Irish horseracing between 2016 and 2024, 2) establish injury characteristics, 3) compare incidence rates between professional and amateur racing and 4) investigate changes in incidence rates over time.